Meta-analysis of epigenome-wide associations between DNA methylation at birth and childhood cognitive skills - Caramaschi, Doretta; Neumann, Alexander; Cardenas, Andres; Tindula, Gwen; Alemany, Silvia; Zillich, Lea; Pesce, Giancarlo; Lahti, Jari M. T.; Havdahl, Alexandra; Mulder, Rosa; Felix, Janine F.; Tiemeier, Henning; et al. (Molecular psychiatry, 2022)
Cognitive skills are a strong predictor of a wide range of later life outcomes. Genetic and epigenetic associations across the genome explain some of the variation in general cognitive abilities in the general population and it is plausible that epigenetic associations might arise from prenatal environmental exposures and/or genetic variation early in life. We investigated the association between cord blood DNA methylation at birth and cognitive skills assessed in children from eight pregnancy cohorts within the Pregnancy And Childhood Epigenetics (PACE) Consortium across overall (total N = 2196), verbal (total N = 2206) and non-verbal cognitive scores (total N = 3300). The associations at single CpG sites were weak for all of the cognitive domains investigated. One region near DUSP22 on chromosome 6 was associated with non-verbal cognition in a model adjusted for maternal IQ. We conclude that there is little evidence to support the idea that variation in cord blood DNA methylation at single CpG sites is associated with cognitive skills and further studies are needed to confirm the association at DUSP22.
Gesehen am 12.03.2024